2004
DOI: 10.17221/4026-pse
|View full text |Cite
|
Sign up to set email alerts
|

Factors affecting nitrogen concentration in spring oilseed rape (Brassica napus L.)

Abstract: The effect of the duration of the growth season, meaning daily temperature, precipitation rate, growing degree in days, nitrogen rates and application time, stand population density, soil nitrogen content and the interaction among these factors on nitrogen concentration in spring oilseed rape plants of aboveground dry ma�er. During the vegetative growth season, mature seeds and straw were studied in field experiment with spring oilseed rape (Brassica napus L.) cv. Star over five years. It was found that nitrog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
25
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 14 publications
1
25
0
Order By: Relevance
“…Although rapeseed yields varied with different environmental variables [28], there was only one season's result, the experiments were located in different counties, and the weather conditions at the specific sites were different. Indeed, further pairing experiments depending on soil characters and weather conditions should also be performed to study the critical processes of soil nutrient supply in different rotations.…”
Section: Seed Yield and Yield Responses To Fertilizer Applicationsmentioning
confidence: 99%
“…Although rapeseed yields varied with different environmental variables [28], there was only one season's result, the experiments were located in different counties, and the weather conditions at the specific sites were different. Indeed, further pairing experiments depending on soil characters and weather conditions should also be performed to study the critical processes of soil nutrient supply in different rotations.…”
Section: Seed Yield and Yield Responses To Fertilizer Applicationsmentioning
confidence: 99%
“…Zhang et al (2006) also reported that the average height of rape suitable for mechanized harvesting was about 160 cm. LD planting promoted plant growth and development, which led to taller and bigger plants with more branches and pods per plant, and required more N than HD planting (Sidlauskas and Tarakanovas 2004;Leach et al 1999). Plants grown at higher densities are thinner, carry fewer branches and fewer pods, and are more tidy in plant structure type than those grown in low densities (Mobasser et al 2008).…”
Section: Optimum Planting Density Contributes To Mechanized Harvestinmentioning
confidence: 99%
“…However, plant requirements for N vary with cultivar, growth stage of plant, N utilization efficiency, soil type, climate, and type of N application (Sidlauskas and Bernotas, 2003; Berry et al, 2010). Previous studies aimed to optimize the rate of N to increase rapeseed yield (Kazemeini et al, 2010).…”
Section: Introductionmentioning
confidence: 99%